1991
DOI: 10.1002/j.1556-6676.1991.tb01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cultural Worldview to Generic Counseling and Development

Abstract: A brief review of the major advances in multicultural counseling and psychotherapy literature and research is presented. A major emphasis is on the construct of “worldview” and on how knowledge and understanding of client worldview leads to more effective, ethical, sensitive, and client‐specific counseling and development activities and interventions. This article reviews research and theory to support use of the worldview construct as a mediating variable in counseling and development interventions. This info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 27 publications
0
84
0
2
Order By: Relevance
“…Therefore, it has been suggested that there is a need to explore the issue of intercultural empathy. Ibrahim (1991) identified the need to "convey empathy in a culturally consistent and meaningful manner" when working with culturally diverse group.…”
Section: Intercultural Awareness Vs Intercultural Empathymentioning
confidence: 99%
“…Therefore, it has been suggested that there is a need to explore the issue of intercultural empathy. Ibrahim (1991) identified the need to "convey empathy in a culturally consistent and meaningful manner" when working with culturally diverse group.…”
Section: Intercultural Awareness Vs Intercultural Empathymentioning
confidence: 99%
“…It is contended that gender identity is anchored within one's primary and secondary cultural context (Ibrahim, 1992b (Brown, 1990b (Ibrahim & Kahn, 1987;Ibrahim & Owen, 1992). This is a culturally based variable that derives from our socialization process and is culturally based (Ibrahim, 1993 Worldview assessment can be conducted using the Scale to Assess World View (SAWV; Ibrahim & Kahn, 1987;Ibrahim, 1991Ibrahim, , 1993 (Kluckhohn, 1956(Kluckhohn, , 1951 (Lonner & Ibrahim, 1989 Sociopolitical history refers to the aspects of the world that we are &dquo;born into&dquo; and which we are expected to learn or accept in order to become normal functioning members of society (Brislin, 1981). Samovar and Porter (1985) state that the experiential backgrounds that people bring into a social context will affect their behavior in those encounters.…”
Section: Gender Identitymentioning
confidence: 99%
“…These cognitions and affect are influenced in turn by one's culture, familial, and primary and secondary group memberships (Ibrahim, 1991) that create specific cultural and cognitive styles (Ramirez & Castaneda 1974 …”
mentioning
confidence: 99%
“…Strongly influenced by culture, worldview consists of the beliefs and assumptions one holds about the world. These beliefs and assumptions inevitably influence the goals, behaviors, problem-solving methods, conflict resolution activities, and decision-making processes that shape interactions and practices within the larger environment (Ibrahim, 1991). Sue (1978) highlighted that the perceived relationship one develops with nature, institutions, people, and objects is a function of worldview.…”
Section: Conclusion: Worldview Development and Multicultural Perspectmentioning
confidence: 99%